APPLICATION OF CALIBRATION CERTIFICATE OF DIGITAL LEVELING SYSTEMS IN THE MONITORING OF STRUCTURES: A CASE STUDY AT THE GOVERNADOR JOSÉ RICHA HYDROELECTRIC POWER PLANT - PR - Gemin, Alyne Raminelli Siguel; Matos, Érica Santos; Faggion, Pedro Luís (Boletim de Ciências Geodésicas, 2018)
The monitoring of the vertical behavior of benchmarks installed in the dam crest of the Governador José Richa hydroelectric power plant (UHGJR) has been performed by the first-order differential leveling method with the use of digital leveling systems which are composed of a digital level and a invar barcode rod. By default, the scales of these instruments are the same, but over time both can change, degrading the observations. In the past, the simultaneous calibration of these systems was not considered in the determination of UHGJR settlements, however, after the development of the first calibration system of digital leveling systems in Brazil, it was possible to investigate the equipment performance as well as to determine a scale factor to be applied to correct the level readings. The results achieved are the systems calibration used in the monitoring of the UHGJR and the calibration certificate application in leveled sections in November 2016. The maximum correction applied to the elevation differences was of the order of nine tenths of millimeters, result attributed to the region observed in the rod, since the deviations obtained in the calibration vary according to the reading position at the rod.